Redox Regulation of the Actin Cytoskeleton in Cell Migration and Adhesion: On the Way to a Spatiotemporal View - Balta, Emre; Kramer, Johanna; Samstag, Yvonne (Frontiers in Cell and Developmental Biology, 2021)
The actin cytoskeleton of eukaryotic cells is a dynamic, fibrous network that is regulated by the concerted action of actin-binding proteins (ABPs). In particular, rapid polarization of cells in response to internal and external stimuli is fundamental to cell migration and invasion. Various isoforms of ABPs in different tissues equip cells with variable degrees of migratory and adhesive capacities. In addition, regulation of ABPs by posttranslational modifications (PTM) is pivotal to the rapid responsiveness of cells. In this context, phosphorylation of ABPs and its functional consequences have been studied extensively. However, the study of reduction/oxidation (redox) modifications of oxidation-sensitive cysteine and methionine residues of actin, ABPs, adhesion molecules, and signaling proteins regulating actin cytoskeletal dynamics has only recently emerged as a field. The relevance of such protein oxidations to cellular physiology and pathophysiology has remained largely elusive. Importantly, studying protein oxidation spatiotemporally can provide novel insights into localized redox regulation of cellular functions. In this review, we focus on the redox regulation of the actin cytoskeleton, its challenges, and recently developed tools to study its physiological and pathophysiological consequences.